JENIS TUMBUHAN YANG DIMANFAATKAN SEBAGAI SUMBER PANGAN OLEH MASYARAKAT DESA JAWAI LAUT KECAMATAN JAWAI SELATAN KABUPATEN SAMBAS - Liza, Liza; Oramahi, H A; Sisillia, Lolyta (Universitas Tanjungpura, 2020)
The plant's species which used as a food source by humans that contains carbohydrates and can produce energy as a source of protein, vitamins, fats, and minerals. The purposes of this research were to obtain the data of the species of plants used as food sources and also to obtain data on the plant parts and how to process these plants as food sources used in Jawai Laut Village, South Jawai District, Sambas Regency. The data is collected by using a survey method through semi-structured interviews with the respondents using a purposive sampling technique. The results of the research found that 58 species of plants belonging to 30 families. Most of them are in the family of Arecaceae, Solanaceae, Moraceae 4 species. The part used is the fruit of 40 species (56%). The plants used as vegetables, spices, and beverage ingredients. There are 28 species (41%) of plants which used by direct consumption, 35 species (51%) of cooked plants, 3 species (4%) of mashed plants, 3 species (4%) of mined plants, and most of the plants which used are from the fruit group, there are 34 species ( 59%), 12 species of vegetables (21%). Food plants are obtained from the cultivation of 48 species (79%), and wild plants 19 species (30%).Keyword: Food sources, Jawai Laut Village, Plant species